ADOPSI STANDAR INDIKASI GEOGRAFIS OLEH PETANI KOPI ROBUSTA DI KABUPATEN TEMANGGUNG - Sumarjo, Nuning Setyowati; Ihsaniyati, Hanifah Ihsaniyati; Pardono, Pardono Pardono (Jurnal AGRISEP, 2020)
Coffee is a superior commodity that has a big role in the Indonesian economy. Temanggung Regency is one of the regions in Central Java that has a high coffee production and broad market share, especially for Robusta coffee. The quality of coffee is determined by geographical factors, the process of cultivation and post harvest processing. Geographical indications are expected to create the unique character of Temanggung robusta coffee. Geographical Indication Standards for Temanggung Robusta Coffee have been prepared. This study aims to identify the level of adoption of Temanggung Robusta coffee IG standards, identify farmers' perceptions of the benefits and constraints in the adoption of Temanggung Robusta coffee IG standards. The research method used descriptive method. Data was collected using a survey with a number of respondents 220 farmers spread across 11 subdistricts Robusta coffee centers. The data analysis method used the scoring method. The results showed that overall the level of adoption of IG standards by coffee farmers was still at the interested stage, although for some standards it had already reached the evaluation, tried and even adoption stages. Farmers have a very high perception of the benefits of adopting IG standards. But, on the other hand farmers still feel constrained in adopting IG standards because farmers are still constrained by high costs, greater labor and time and no price guarantees for coffee produced according to IG standards Collaboration with the government, the private sector, universities and MPIG is needed to provide education, facilitation and assistance in the process of adopting IG standards in order to produce good quality, unique coffee and high competitiveness